Keefektifan Penggunaan Model Pembelajaran Contextual Teaching And Learning Dalam Meningkatkan Hasil Belajar Pembelajaran Bahasa Inggris Mahasiswa - Yandry Diana Dethan; Renold Harse Modok (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The purpose of this study is to describe the effectiveness of applying the Contextual Teaching and Learning (CTL) learning model in improving students' English learning outcomes. This study used narrative literature review method. Thus, the data in this study were collected from eight research journals applied CTL learning model in improving English learning outcomes, in general, and learning outcomes in listening, speaking, and writing materials, in particular. The eight research journals were published research. The results of the study showed that the Contextual Teaching and Learning (CTL) learning model was effective in improving student learning outcomes in learning English. Therefore, this learning model can be an alternative choice for improving student learning outcomes in English learning classroom. However, success in using CTL is very dependent on the material chosen and the person/teacher who uses it in the classroom. So, the teacher needs to understand well the teaching learning model before it is applied in the classroom.